The scientific Muslim : understanding Islam in a new light - Parvaiz, Mohammad Aslam (New Delhi Konark Publishers Pvt Ltd., 2021)
This book deals with Mohammadnism
Includes bibliographical references and index.
Keywords: Qurʼan and science; Muslims